Knowledge and attitude regarding HIV/AIDs among sexual minorities of Kathmandu - Sharma, Sumitra (Journal of Kathmandu Medical College, 2017)
Background: Sexual minorities are at high risk of contracting and spreading HIV/AIDS. Several studies in Nepal and around the world depict issues of HIV/AIDS and other problems of sexual minorities.Objective: The present study was carried out with the aim to investigate and evaluate knowledge and attitude of sexual minorities regarding HIV/AIDS.Methods: A cross-sectional study was conducted for a period of eight months starting from June 2009. Sixty six respondents accomplished quantitative interviews and face-to-face interviewer-administered demographic, knowledge and attitude of HIV/AIDS survey. Descriptive and inferential analysis was done using Statistical Package for Social Sciences version 16. A five point Likert scale was used to assess attitude of the respondents. Pearson’s chi-square test was used to compare the association between knowledge and selected socio-demographic variables. Spearman’s correlation test was used to make out the degree of relationship between knowledge and attitude.Results: Among 66 sexual minorities, 34.84% were gay, 28.78% were transgender, 25.75% were bisexuals and 10.60% were lesbians. Nearly 47% of the respondents showed adequate knowledge with mean knowledge score of 29. With the mean attitude score of 39, 45.5% showed positive attitude towards HIV infection. The findings depicted an association between knowledge and participation of respondents on training/awareness program (p